Rational design, synthesis, and structure–activity relationships of 5-amino-1H-pyrazole-4-carboxylic acid derivatives as protein tyrosine phosphatase 1B inhibitors. Issue 1 (1st January 2017) - Basu, Sujay; Prathipati, Philip; Thorat, Sachin; Ansari, Shariq; Patel, Meena; Jain, Vaibhav; Jinugu, Ramana R.; Niranjan, Sanjay; De, Siddhartha; Reddy, Satyanarayana
Graphical abstract: Abstract: A series of novel amino-carboxylic based pyrazole as protein tyrosine phosphatase 1B (PTP1B) inhibitors were designed on the basis of structure-based pharmacophore model and molecular docking. Compounds containing different hydrophobic tail (1, 2-diphenyl ethanone, oxdiadizole and dibenzyl amines) were synthesized and evaluated in PTP1B enzymatic assay. Structure–activity relationship based optimization resulted in identification of several potent, metabolically stable and cell permeable PTP1B inhibitors.